In vivo analysis of synaptic degeneration with Aβ plaque and NFT accumulation in cognitive decline. (31st December 2021) - DiFilippo, Alexandra H.; Tullis, Tyler; Zammit, Matthew D.; Murali, Dhanabalan; Kohli, Akshay; Ennis, Gilda E.; Davenport, Nancy J.; Barnhart, Todd E.; Engle, Jonathan W.; Betthauser, Tobey J.; Stone, Charles K.; Johnson, Sterling C.; et al.
Abstract: Background: [ 11 C]UCB‐J selectively binds to synaptic vesicle glycoprotein 2A (SV2A) and may be used to measure synaptic density in synaptopathies. Along with the accumulation of amyloid‐b plaques and neurofibrillary tau tangles, neurodegeneration is a hallmark of Alzheimer's disease (AD) dementia. Synaptic density may be decreased due to AD pathology, resulting in cognitive dysfunction. We examined whether synaptic density was related to the accumulation of protein aggregates characteristic of AD as well as cognitive function. Method: Thirty subjects (68.6±6.2 years old, 20F/10M) recruited from the Wisconsin ADRC and the Wisconsin Registry for Alzheimer's Prevention study underwent [ 11 C]UCB‐J dynamic PET imaging to assess synaptic density, T1w‐MR imaging, and the Rey Auditory Verbal Learning Test (RAVLT). Twenty‐four participants also completed [ 11 C]PiB dynamic imaging to assess amyloid‐b plaque accumulation and [ 18 F]MK‐6240 dynamic imaging to assess neurofibrillary tangle accumulation. T1w‐MRI was used to derive subject‐specific regions of interest (ROIs) as well as to calculate the matrices required to transform images into MNI152 space. Global amyloid burden was ascertained by taking the mean PiB DVR across eight bilateral AAL‐based ROIs. Neurofibrillary tau tangle accumulation in the entorhinal cortex was quantified using the [ 18 F]MK‐6240 SUV ratio. Subject‐specific hippocampus ROIs for [ 11 C]UCB‐J analysis were defined using FreeSurfer (v7) segmentation of the participant's MR image. Result: Using data from the n=24 subjects, [ 11 C]UCB‐J binding in the hippocampus was significantly associated with [ 11 C]PiB global DVR (R 2 = 0.24, P = 0.01) and [ 18 F]MK‐6240 uptake in the entorhinal cortex (R 2 = 0.17, P = 0.04). After correcting for hippocampus volume size, significance decreased for both measures (R 2 = 0.28, P = 0.05 for [ 11 C]PiB global DVR; R 2 = 0.17, P = 0.05 for [ 18 F]MK‐6240 entorhinal cortex SUVR). [ 11 C]UCB‐J binding in the hippocampus was not significantly related to RAVLT immediate recall (R 2 = 0.52, P = 0.08) but was significantly associated with RAVLT delayed recall (R 2 = 0.55, P = 0.04). Conclusion: Findings suggest that synaptic impairment is related to amyloid‐b and neurofibrillary tau tangle accumulation as well as worse performance on RAVLT delayed recall. Future work will test the longitudinal relationship between accumulation of AD pathology, synapse loss, and cognitive decline.